Repeated seizure-induced brainstem neuroinflammation contributes to post-ictal ventilatory control dysfunction - Osmani, Wasif A.; Gallo, Alexander; Tabor, Madeline; Eilbes, Melissa; Cook-Snyder, Denise R.; Hodges, Matthew R. (Frontiers in Physiology, 2024)
Patients with epilepsy face heightened risk of post-ictal cardiorespiratory suppression and Sudden Unexpected Death in Epilepsy (SUDEP). Studies have shown neuroinflammation, mediated by the activation of microglia and astrocytes, may be both a cause or consequence of seizure disorders. Kcnj16 (Kir5.1) knockout rats (SS kcnj16-/-) are susceptible to repeated audiogenic seizures and recapitulate features of human SUDEP, including a post-ictal ventilatory suppression which worsens with repeated seizures and seizure-induced mortality. Here, we tested the hypothesis that repeated seizures cause neuroinflammation within key brainstem regions that contribute to the control of breathing. Audiogenic seizures were elicited once/day for up to 10 days in groups of adult male SS kcnj16-/-rats, from which frozen brainstem biopsies of the pre-Bötzinger complex/nucleus ambiguous (preBötC/NA), Bötzinger complex (BötC), and Raphe Magnus (RMg) regions were subjected to a cytokine array. Several cytokine/chemokines, including IL-1α and IL-1ß, were increased selectively within preBötC/NA after 3 or 5 days of seizures with fewer changes in other regions tested. In additional groups of male SS kcnj16-/-rats that underwent repeated seizures, we quantified microglial (IBA-1+) cell counts and morphology specifically within the preBötC/NA region and showed increased in microglial cell counts, area and volume consistent with microglial activation. To further test a role of inflammation in physiological responses to seizures and seizure-related mortality, additional groups of SS kcnj16-/-rats were treated with anakinra (IL-1R antagonist), ketoprofen (non-selective COX inhibitor) or saline for 3 days before and up to 10 days of seizures (1/day) and breathing was measured before, during and after each seizure. Remarkably, IL-1R antagonism mitigated changes in the post-ictal ventilatory suppression on Days 7-10 but failed to prevent seizure-related mortality, whereas ketoprofen treatment exacerbated post-ictal ventilatory suppression compared to other treatment groups but prevented seizure-related mortality. These data demonstrate neuroinflammation and microglial activation within a key brainstem region of respiratory control following repeated seizures, which may functionally but differentially contribute to the pathophysiological consequences of repeated seizures.